Body mass index in medicine students: Relationship with stress, eating habits and physical activity: Índice de masa corporal en estudiantes de medicina: Relación con estrés, hábitos alimenticios y actividad física - Aguilar-Ydiáquez, Claudia (2022)
Introduction: The Changes in lifestyles predispose university students to face constant stressful situations and to modify their eating habits and physical activity, with possible alterations in the body mass index. Objective: To evaluate the relationship between body mass index and stress, physical activity and eating habits in medical students. Methods: Cross-sectional descriptive observational study. 306 medical students participated from first to sixth year: 153 with normal weight, 121 with overweight and 32 with obesity, average age 21,95 years. The body mass index was considered and the questionnaires were applied: Global Perception of Stress Scale for University Students (Adapted in Peruvian university students), International Physical Activity Questionnaire and the modified Reyes Food Frequency Questionnaire, using Google software Forms. Results: The proportion of normal weight was 50%, overweight 39,50% and obese 10,50%. According to eating habits, people with body mass index significantly increased their consumption of soft drinks (p = 0,030), meat (p = 0,017) and alcohol (p = 0,005), more frequent breakfast (p = 0,037) and less consumption of legumes (p = 0,049). The levels of distress were lower in the obese (p = 0,055); there was no significant difference in physical activity. Conclusions: The elevation of the body mass index in medical students was associated with inadequate eating habits. Low levels of distress and physical activity were more frequent in obese people, although without significant difference.